Disaster debris management during the 2014-2015 Malaysia flood incident - Syed Ismail, Sharifah Norkhadijah; Zainal Abidin, Emilia; Hashim, Zailina; Rasdi, Irniza; How, Vivien; Praveena, Sarva Mangala; Karuppiah, Karmegam; Ho, Yu Bin; Ismail, Suriani; Mohamad, Syukriah; Nik Azme, Nik Nurul Aizzah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Flood is a natural disaster cause by heavy rainfall and high tide phenomenon. In the event of flood, substantial amount of wastes tend to be moved away and washed with mud that cause the task of waste recovering extremely challenging. The objective of the study was to assess flood victims participation, duration and major problem arise during post flood waste clean-up activity together with respondent’s knowledge and psychological importance in the recovery process. Methods: A cross sectional survey using interview and self-administered questionnaire was conducted involving 150 flood victims in Kuala Krai, Kelantan, who were heavily affected by the recent flood. Results: Respondents participation in the clean-up process was high (N = 126, 84%). Average 1 to 3 months were taken for the clean-up activity. Majority of the respondents had low and moderate satisfaction on the cleaning service provided by the authority (N = 84, 56%). Major problem arises from the past flood waste clean up activity was the biased waste removal process (N = 124, 83%), victims have to find alternative ways for disposal (N = 108, 72%) and the temporary disposal site were located near to the housing area that creates discomfort (N = 105, 70%). The correlation test obtained significant relationship between knowledge and education level (X2 = 0.203, p=0.013). But no significant relationship was obtained between knowledge with gender, age, monthly income, duration of clean-up process, respondents participation and satisfaction. Conclusion: Disaster debris management and disposal is critically important to support the victims in their recovery process.